2015
DOI: 10.12911/22998993/60464
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Pollution Removal From Domestic Wastewater in Constructed Wetland Systems With Vertical Flow With Common Reed and Glyceria Maxima

Abstract: The paper presents the results of research on the effects of removing pollution from domestic wastewater in two beds of constructed wetland systems with vertical flow. Bed I was planted with common reed (Phragmites australis Cav. Trin. Ex Steud.), whereas bed II with Glyceria maxima (Glyceria aquatica L.). The surface of each of the beds amounted to 30 m 2 , and the hydraulic load of each of them amounted to 0.033 m 3 •m-2 •d-1. The study showed very good results in the removal of most of the analyzed indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The statistical analysis revealed that the number of bacteria in the sewage pretreated in the septic tank and then entering the columns was similar to that reported by other authors [3,5]. The value >0.5 of the ratio of BOD 5 /COD Cr in the wastewater flowing to the pre-treated columns indicates the presence of the easily degradable organic substances in biochemical processes [20,21] (Table 1).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The statistical analysis revealed that the number of bacteria in the sewage pretreated in the septic tank and then entering the columns was similar to that reported by other authors [3,5]. The value >0.5 of the ratio of BOD 5 /COD Cr in the wastewater flowing to the pre-treated columns indicates the presence of the easily degradable organic substances in biochemical processes [20,21] (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…This problem involves not only the wastewater from municipal wastewater treatment plants (WTP) but also treated sewage discharged from on-site sewage treatment facilities. Research shows that the removal of indicator bacteria in a septic tank/leach _________________________ drains or soil-plant system is insufficient as evidenced by the presence of Escherichia coli and coliform bacteria in the wastewater treated in these systems [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative characteristics of pre-treated sewage flowing into filtration beds are presented in Table 1. On the basis of statistical analysis, it can be concluded that biogenic indicators in the sewage inflowing to individual filtration columns remained at a level similar to that reported in literature [Kaczor and Bugajski 2006, Kaczor 2009, Dębska et al 2015, Obarska-Pempkowiak and others. 2015.…”
Section: Research Results and Analysissupporting
confidence: 81%
“…The water resources on the Earth participate in an ever-recurring hydrological cycle that connects the atmosphere, the lithosphere, and the hydrosphere. In Poland, per capita water availability is 1.600 m 3 (22nd place in Europe). Because the water reserves of Poland are small, water should be managed rationally and economically, in accordance with the principles of sustainable development [Małecki&Gołębiak, 2012].…”
Section: Introductionmentioning
confidence: 99%